Types of intra- and extrafusal muscle fibre innervated by dynamic skeleto-fusimotor axons in cat peroneus brevis and tenuissimus muscles, as determined by the glycogen-depletion method. - Barker, D (1977)
1. The types of intra- and extrafusal muscle fibre innervated by dynamic skeleto-fusimotor (beta) axons were determined by using a modification of the glycogen-depletion method of Edström & Kugelberg (1968) combined with histochemical tests for various enzyme reactions. A single beta axon was prepared in each of the experiments, which were carried out on six peroneus brevis and two tenuissimus muscles. 2. The intrafusal distribution of dynamic beta axons is almost exclusively restricted to bag1 fibres. The bags fibre was depleted in each of twenty-four beta-innervated spindle poles; the only fibres of a different type depleted intrafusally were a bag2 fibre in one pole and a long chain in another. 3. Depletion in the bag1 fibres was usually restricted to one zone in one pole, generally in a mid-polar location. 4. The extrafusal muscle fibres depleted by dynamic beta axons belong to the slow oxidative type as defined by Ariano, Armstrong & Edgerton (1973). The number of such fibres in each motor unit could not be accurately determined, but is almost certainly small. 5. The slow oxidative muscle fibres innervated by dynamic beta axons were not depleted over their entire length. Since there is no reason to assume that they are not twitch fibres, it would seem that the localized depletions result from the conditions required to obtain glycogen depletion, i.e. long periods of motor stimulation applied during the occlusion of the muscle's blood supply. Under similar experimental conditions depletion of glycogen was also restricted to portions of fibres in fast oxidative-glycolytic motor units, but extended over most of the length of the fibres in fast glycolytic units.